Nutrition : - Grosvenor, Mary B. (John Wiley & Sons, Inc., 2002)
NUTRITION: FROM SCIENCE TO LIFE helps students apply the science of nutrition to their personal and professional lives. Like many introductory nutrition texts, this book offers fundamental information regarding nutrients, their functions in the body, and their sources in diet. The author enhances this foundation by providing the scientific story behind nutrition issues. As a result, students acquire not only a command of the essentials, but also the ability to think critically about the nutrition issues that they will encounter as consumers and as professionals.